1998
DOI: 10.1007/bf02828927
|View full text |Cite
|
Sign up to set email alerts
|

Charges in gauge theories

Abstract: In this article we investigate charged particles in gauge theories. After reviewing the physical and theoretical problems, a method to construct charged particles is presented. Explicit solutions are found in the Abelian theory and a physical interpretation is given. These solutions and our interpretation of these variables as the true degrees of freedom for charged particles, are then tested in the perturbative domain and are demonstrated to yield infra-red finite, on-shell Green's functions at all orders of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 60 publications
2
30
0
Order By: Relevance
“…We further note that (13) is essentially identical to the result [6,8] Having thus shown the cancellation of the various IR divergences which occur in the residue of the propagator evaluated in wave-function, on-shell renormalisation, let us move on to a charge being scattered off a source. For the covariant diagram, 4e, we again take the p / + m numerator factors through the interaction vertex γ matrices and only retain those terms which have a pole for each external leg.…”
Section: A) Propagating Chargessupporting
confidence: 62%
See 1 more Smart Citation
“…We further note that (13) is essentially identical to the result [6,8] Having thus shown the cancellation of the various IR divergences which occur in the residue of the propagator evaluated in wave-function, on-shell renormalisation, let us move on to a charge being scattered off a source. For the covariant diagram, 4e, we again take the p / + m numerator factors through the interaction vertex γ matrices and only retain those terms which have a pole for each external leg.…”
Section: A) Propagating Chargessupporting
confidence: 62%
“…It will be shown that the IR divergences associated with going on-shell are indeed removed already at the level of S-matrix elements at all orders in perturbation theory. (Some similar results for scalar QED have been announced elsewhere [5,6]; here we consider the fermionic theory and give details of our calculations and techniques.) Then the UV structure of these fields will be investigated and it will be shown that the dressed fields have a good UV behaviour.…”
Section: Introductionsupporting
confidence: 60%
“…The asymptotic dynamics of this theory [20] requires further study, in particular the physical asymptotic fields need to be constructed. Finite temperature field theory is another area where infra-red divergences are important, here, of course, the residual asymptotic dynamics of zero temperature will be acerbated by excitations from the heat bath.…”
Section: Discussionmentioning
confidence: 99%
“…with the obvious meaning given to the components of J µ defined in (20). We shall work in Feynman gauge and take the plane wave expansions given by…”
Section: Scalar Qed: the Four Point Interactionmentioning
confidence: 99%
See 1 more Smart Citation